Mechanisms of alkaliptosis - Chen, Fangquan; Kang, Rui; Liu, Jiao; Tang, Daolin (Frontiers in Cell and Developmental Biology, 2023)
Malignant tumors represent a major threat to global health and the search for effective treatments is imperative. While various treatments exist, including surgery, radiotherapy, chemotherapy, immunotherapy and combination therapies, there remains a need to develop therapies that target regulated cell death pathways to eliminate cancer cells while preserving normal cells. Alkaliptosis, a pH-dependent cell death process triggered by the small molecular compound JTC801, has been identified as a novel approach for malignant tumor treatment, particularly in pancreatic cancer. Two major signaling pathways, the NF-κB-CA9 pathway and the ATP6V0D1-STAT3 pathway, contribute to the induction of alkaliptosis. This review summarizes recent developments in our understanding of alkaliptosis signals, mechanisms, and modulation, and explores its context-dependent effects on drug resistance, inflammation, and immunity. By providing a deeper understanding of the heterogeneity and plasticity of cell death mechanisms, this information holds promise for informing the design of more effective anti-tumor therapies.